Water Resources and Governance Approaches: Insights for Achieving Water Security - Natalia Julio; Ricardo Figueroa; PONCE OLIVA, ROBERTO DANIEL (My University, 2021)
Integrated river basin management (IRBM) has been proposed as a means to achieve water security (WS), maximizing economic and social well-being in an equitable manner and maintaining ecosystem sustainability. IRBM is regulated by a governance process that benefits the participation of different actors and institutions; however, it has been difficult to reach a consensus on what good governance means and which governance perspective is better for achieving it. In this paper, we explore the concept of “good water governance” through the analysis of different governance approaches: experimental (EG), corporate (CG), polycentric (PG), metagovernance (MG) and adaptive (AG) governances. We used the Organisation for Economic Co-operation and Development (OECD) water governance dimensions (effectiveness, efficiency and trust and engagement) as a “good enough water governance” that regards water governance as a process rather than an end in itself. Results indicate that each of the five governance theories presents challenges and opportunities to achieve a good governance process that can be operationalized through IRBM, and we found that these approaches can be adequately integrated if they are combined to overcome the challenges that their exclusive application implies. Our analysis suggests that a combination of AG and MG encompasses the OECD water governance dimensions, in terms of understanding “good enough water governance” as a process and a means to perform IRBM. In order to advance towards WS, the integration of different governance approaches must consider the context-specific nature of the river basin, in relation to its ecologic responses and socioeconomic characteristics.
Keywords: water management; integrated river basin management; water security; good governance; international cooperation; rivers; watersheds; ecosystem sustainability; good governances; integrated river basin managements; metagovernance; organization for economic co-operation and development; social well-being; water governance; water security; waters managements; waters resources; basin management; governance approach; oecd; river basin; sustainability; water management; water resource; water management